1999
DOI: 10.1093/ps/78.6.873
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of four endogenous viral genes in semi-congenic lines of meat chickens

Abstract: Restriction fragment length polymorphism analyses were used to examine endogenous viral genes (ev genes or ALVE genes) of the avian leukosis viral (ALV) family in semi-congenic lines of meat chickens. The Generation 6 lines examined in this study were semi-congenic in that each contained birds with either zero or with one ALVE gene in hemizygous state plus some solitary long terminal repeat (LTR) elements. Using four restriction enzymes on chicken genomic DNA and two probes, one representing the entire ALV ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Previous work by Grunder et al (1999) used Southern blot analysis to assess the structural completeness of the broiler-derived elements used in this study. Their work suggested that all three elements (ALVE-B9, ALVE-B10 and ALVE-B11) were full length, at least within the resolution of the Southern blot assay used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by Grunder et al (1999) used Southern blot analysis to assess the structural completeness of the broiler-derived elements used in this study. Their work suggested that all three elements (ALVE-B9, ALVE-B10 and ALVE-B11) were full length, at least within the resolution of the Southern blot assay used.…”
Section: Resultsmentioning
confidence: 99%
“…Studies based on Southern blot analysis using a variety of lines of chickens suggested the existence of at least 20 unique elements (Hughes et al, 1979;Astrin et al, 1980;Gudkov et al, 1981;Humphries et al, 1984;Crittenden, 1991;Sabour et al, 1992). More recent evidence suggests that there are 50 or more different ALVE loci in various lines of chicken (Benkel, 1998).…”
Section: Introductionmentioning
confidence: 99%